Sexism and violence in dating relationships among adolescents in Lima - Manrique Tapia, César Raúl (2021)
The purpose of the study was to determine the relationship between sexism and violence committed and suffered in dating relationships in adolescents between 15 and 17 years of age from North Lima. The sample consisted of 93 adolescents, for which the type of research was applied and the non-experimental cross-sectional design. The instruments used were; the Detection Scale of Sexism in Adolescents (DSA) and the Inventory of violence in dating relationships among adolescents (CADRI). The results show that sexism is correlated in a direct and significant way with the violence committed, and in a non-significant and direct way with the violence suffered, in a low degree for both.